1994
DOI: 10.1111/j.1442-1984.1994.tb00098.x
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Queen Bumble Bees as Pollinators Facilitating Inter‐morph Crossing inPrimula sieboldii

Abstract: Flower‐visiting insects, the distribution of pollen on an insect's body, and fruit and seed sets of Primula sieboldiiE. Morren were investigated in a maritime deciduous forest habitat of the Hidaka region in Hokkaido. Queens of Bombus diversus tersatus Smith (Hymenoptera: Apidae), Bombus schrencki albidopleuralis Skorikov, and Bombus deuteronymus deuteronymus Schulz were observed to visit the flowers of the species. Bumblebee claw marks were found on the flower petals of 68% of the flowering ramets of the spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 18 publications
2
64
0
Order By: Relevance
“…Primula sieboldii flowers in the spring (from May to June) and is mainly pollinated by long‐tongued queen bumblebees (Washitani et al . 1994).…”
Section: Methodsmentioning
confidence: 99%
“…Primula sieboldii flowers in the spring (from May to June) and is mainly pollinated by long‐tongued queen bumblebees (Washitani et al . 1994).…”
Section: Methodsmentioning
confidence: 99%
“…For example, flower visitation can be easily determined in orchids (Nilsson 1992;Pauw 2007) and certain milkweeds (Ollerton & Liede 1997) by quantifying pollinaria removal. In other plant species tripped flowers (Parker 1997) or bumble bee claw marks allow rapid assessment of visitation rates (Washitani et al 1995). Similarly it has been suggested that the probing beak of a visiting sunbird could disturb the anther ring of bird-pollinated Erica flowers (Rebelo et al 1985;Schumann et al 1992).…”
Section: Introductionmentioning
confidence: 97%
“…Leaf emergence and flowering occur in April to May, and the plant fruits in July. Each flowering ramet has 1 to 13 flowers on a 10-to 30-cm flower stalk, and the main pollinator is the queen bumblebee, Bombus diversus tersatus Smith (Washitani et al 1995). Although Bombylius major and Rhingia laevigata visit flowers of P. sieboldii, its frequency is low.…”
Section: Plant Species and Study Sitementioning
confidence: 99%